2006
DOI: 10.1159/000092546
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Current Practices in Fellowship Orientation

Abstract: Background: The transition from medical resident to subspecialty fellow is a critical time period in fellowship training that has not been well described. The current practices of fellow orientation in pulmonary and critical care training programs are not known. Objectives: The aim of this study was to describe orientation practices for training programs in the United States. Methods: A 10-question survey was sent via e-mail to program directors of pulmonary/critical care fellowship programs identified on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Core curriculum training in many institutions includes a series of lectures and modular approach including a variety of technological media describing the procedure, its indications, complications and consenting [6][7][8][9]. For example, trainees may watch a video of a procedure or use a web-based e-learning module such as that available at British Thoracic Society (www.brit-thoracic.org.uk) or Essential Bronchoscopist (www.bronchoscopy.org) web sites [10][11][12].…”
Section: Training In Bronchoscopy Skillsmentioning
confidence: 99%
“…Core curriculum training in many institutions includes a series of lectures and modular approach including a variety of technological media describing the procedure, its indications, complications and consenting [6][7][8][9]. For example, trainees may watch a video of a procedure or use a web-based e-learning module such as that available at British Thoracic Society (www.brit-thoracic.org.uk) or Essential Bronchoscopist (www.bronchoscopy.org) web sites [10][11][12].…”
Section: Training In Bronchoscopy Skillsmentioning
confidence: 99%
“…Training in TBNA has remained a tenet of basic diagnostic bronchoscopy and cTBNA continues to be taught in the majority of PCCM fellowship programs (12), however surveys demonstrate that bronchoscopy education remains quite variable, including the instruction of TBNA (12)(13)(14). Surveys also indicate that cTBNA remains a poorly practiced procedure during and after fellowship (9,10,14,15).…”
Section: Current State Of Transbronchial Needle Aspiration Trainingmentioning
confidence: 99%
“…Furthermore, when clinical responsibilities begin, it can be difficult for subspecialty trainees to attend introductory lectures, potentially making their transition more difficult and conceivably deleteriously affecting patient care. Thus, condensing these introductory lectures into a focused orientation program seems ideal (Lucarelli, Lucey, & Mastronarde, 2007). Although many training programs have orientations, including 50% (Merenstein & Preisach, 2002) to 90% (Brillman, Sklar, & Viccellio, 1995) of family practice and emergency medicine residencies, their curricula vary widely and their impact is largely unknown (Lucarelli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, condensing these introductory lectures into a focused orientation program seems ideal (Lucarelli, Lucey, & Mastronarde, 2007). Although many training programs have orientations, including 50% (Merenstein & Preisach, 2002) to 90% (Brillman, Sklar, & Viccellio, 1995) of family practice and emergency medicine residencies, their curricula vary widely and their impact is largely unknown (Lucarelli et al, 2007). Several small studies of specific orientation programs have been reported.…”
Section: Introductionmentioning
confidence: 99%